Seed banks of native forbs, but not exotic grasses, increase during extreme drought. Issue 4 (1st March 2018) - LaForgia, Marina L.; Spasojevic, Marko J.; Case, Erica J.; Latimer, Andrew M.; Harrison, Susan P.
Abstract: Extreme droughts such as the one that affected California in 2012–2015 have been linked to severe ecological consequences in perennial‐dominated communities such as forests. In annual communities, drought impacts are difficult to assess because many species persist through facultative multiyear seed dormancy, which leads to the development of seed banks. Impacts of extreme drought on the abundance and composition of the seed banks of whole communities are little known. In 80 heterogeneous grassland plots where cover is dominated by ~15 species of exotic annual grasses and diversity is dominated by ~70 species of native annual forbs, we grew out seeds from soil cores collected early in the California drought (2012) and later in the multiyear drought (2014), and analyzed drought‐associated changes in the seed bank. Over the course of the study we identified more than 22, 000 seedlings to species. We found that seeds of exotic annual grasses declined sharply in abundance during the drought while seeds of native annual forbs increased, a pattern that resembled but was even stronger than the changes in aboveground cover of these groups. Consistent with the expectation that low specific leaf area (SLA) is an indicator of drought tolerance, we found that the community‐weighted mean SLA of annual forbs declined both in the seed bank and in the aboveground community, as low‐SLA forbs increased disproportionately. In this system, seed dormancy reinforces the indirect benefits of extreme drought to the native forb community.